Proteomics and lipidomics analyses reveal modulation of lipid metabolism by perfluoroalkyl substances in liver of Atlantic cod (Gadus morhua) - Dale, Karina; Yadetie, Fekadu; Müller, Mette Bjørge; Pampanin, Daniela M.; Gilabert, Alejandra; Zhang, Xiaokang; Haarr, Anne; Tairova, Zhanna; Lille-Langøy, Roger; Jan LudvigLycheb; Porte Visa, Cinta; Karlsen, Odd André; et al. (Aquatic Toxicology, 2020)
The aim of the present study was to investigate effects of defined mixtures of polycyclic aromatic hydrocarbons (PAHs) and perfluoroalkyl substances (PFASs), at low, environmentally relevant (1× = L), or high (20× = H) doses, on biological responses in Atlantic cod (Gadus morhua). To this end, farmed juvenile cod were exposed at day 0 and day 7 via intraperitoneal (i.p.) injections, in a two-week in vivo experiment. In total, there were 10 groups of fish (n = 21-22): two control groups, four separate exposure groups of PAH and PFAS mixtures (L, H), and four groups combining PAH and PFAS mixtures (L/L, H/L, L/H, H/H). Body burden analyses confirmed a dose-dependent accumulation of PFASs in cod liver and PAH metabolites in bile. The hepatosomatic index (HSI) was significantly reduced for three of the combined PAH/PFAS exposure groups (L-PAH/H-PFAS, H-PAH/L-PFAS, H-PAH/H-PFAS). Analysis of the hepatic proteome identified that pathways related to lipid degradation were significantly affected by PFAS exposure, including upregulation of enzymes in fatty acid degradation pathways, such as fatty acid β-oxidation. The increased abundances of enzymes in lipid catabolic pathways paralleled with decreasing levels of triacylglycerols (TGs) in the H-PFAS exposure group, suggest that PFAS increase lipid catabolism in Atlantic cod. Markers of oxidative stress, including catalase and glutathione S-transferase activities were also induced by PFAS exposure. Only minor and non-significant differences between exposure groups and control were found for cyp1a and acox1 gene expressions, vitellogenin concentrations in plasma, Cyp1a protein synthesis and DNA fragmentation. In summary, our combined proteomics and lipidomics analyses indicate that PFAS may disrupt lipid homeostasis in Atlantic cod. This study was funded by Research Council of Norway through the dCod 1.0: decoding the systems toxicology of Atlantic cod project (Center for Digital Life Norway project no. 248840) and the iCod 2.0: Integrative environmental genomics of ...